AN EFFICIENT APPROACH TO THE TEACHING OF ACCOUNTING. - Bowers, Russell (The Accounting Review, 1947)
Abstract In accounting as in almost no other field can the extremes of good and bad education be illustrated. Education in accounting should be subjected to the test of a critical theory. Former theories of education stresses the classical in the sense of the literary, linguistic and the so-called cultural disciplines. Education was conceived as specific training for the work to be undertaken after graduation from school. Great danger lies in this educational philosophy. For purposes of professional education the subject matter should be classed in two categories. While the difference may be one of degree, the distinction at some level is not only sound, it is indispensable. First, there is the skill or knowledge which the student can postpone learning, in the interest of total cost and economy in learning, until he needs to use it. Most of this training is more specific and extensive than colleges can reasonably hope to undertake. Second, there is the skill or knowledge which the student can learn with profit long in advance of his need to use it. Great economy in education can be attained generally if education on the higher professional level is confined to the latter.